2011
DOI: 10.4028/www.scientific.net/kem.488-489.182
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Fatigue Behaviour of Nodular Cast Iron

Abstract: This paper presents an experimental and numerical study on two different types of the nodular cast iron EN-GJS-400-18-LT. The experimental procedure includes symmetrical and unsymmetrical strain controlled tests on the cylindrical specimens as well as crack initiation and propagation tests on the compact tension and single edged notched specimens. Different loading regimes are applied, and monitoring of the crack length during the tests is performed by an optical system. Within the framework of numerical inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Furthermore, comparing corresponding hysteresis loops for the symmetrical and unsymmetrical tests, it can be concluded that mean strain has no significant effect on the cyclic hardening behaviour of the investigated materials. The presented results represent the basis for determination of material parameters of a cyclic plasticity constitutive model like that recently developed by Tonković and Sorić [20][21][22] and damage criterions based on the stabilised accumulated inelastic hysteresis strain energy [22].…”
Section: Uniaxial Monotonic Tensile and Cycle Testsmentioning
confidence: 91%
“…Furthermore, comparing corresponding hysteresis loops for the symmetrical and unsymmetrical tests, it can be concluded that mean strain has no significant effect on the cyclic hardening behaviour of the investigated materials. The presented results represent the basis for determination of material parameters of a cyclic plasticity constitutive model like that recently developed by Tonković and Sorić [20][21][22] and damage criterions based on the stabilised accumulated inelastic hysteresis strain energy [22].…”
Section: Uniaxial Monotonic Tensile and Cycle Testsmentioning
confidence: 91%
“…Material properties of nodular cast iron are well elaborated in previous authors' paper [6,7]. An algorithm which enables numerical modelling of cyclic plasticity behaviour of nodular cast iron is proposed by Čanžar in [8]. The present paper is a continuation of that study where the fatigue damage in the specimen near the notch and the crack tip is analysed in detail for more accurate predictions.…”
Section: Fig 1 Experimental Setup For the Cmod And Crack Propagatiomentioning
confidence: 87%
“…Moreover, comparing corresponding hysteresis loops for the symmetric and asymmetric tests, it may be concluded that mean strain has no significant effect on the cyclic hardening behaviour of the considered material. More data can be found in [8].…”
Section: Uniaxial Cycle Testsmentioning
confidence: 99%
“…In cast iron, process‐related material defects often cannot be avoided. The influence of those defects on fatigue strength of nodular cast iron is investigated 14–20 . In this paper, the focus of the investigations is to determine the influence of the transient material behavior on the calculated damage sum.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of those defects on fatigue strength of nodular cast iron is investigated. [14][15][16][17][18][19][20] In this paper, the focus of the investigations is to determine the influence of the transient material behavior on the calculated damage sum. The influence of defects on fatigue properties was not investigated in this work; therefore, specimens containing major discontinuities were not considered in the evaluation.…”
Section: Introductionmentioning
confidence: 99%